ARTICLE REVIEW: THE TREATMENT PROBLEM AND ADVERSE DRUG REACTIONS IN THE TREATMENT OF MULTIDRUG-RESISTANT TUBERCULOSIS - Sartika Aprianti; Prayudi Santoso; Melisa Intan Barliana; Ivan Surya Pradipta (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Multidrug-resistant tuberculosis (MDR-TB) is the resistance of Mycobacterium tuberculosis to at least two tuberculosis (TB) drugs, rifampicin and isoniazid. The disease requires a long treatment duration with several second-line drugs. This leads to a globally low success rate of approximately 56% for MDR-TB treatment. Studies have reported that adverse drug reactions (ADRs) contribute to high rates of non-compliance, treatment discontinuation, and failure. This narrative review aimed to provide information about MDR-TB treatment modalities, various ADRs, challenges encountered in MDR-TB treatment, and instances of ADRs that can impact treatment success. This narrative review study was conducted by searching for scientific information from the primary electronic databases PubMed and Google Scholar, covering 2012-2022. Based on the literature search results, 14 studies were identified, demonstrating challenges in TB and MDR-TB treatment, along with 6 ADRs that can influence treatment success in MDR-TB patients. ADRs during MDR-TB treatment can affect patients’ physical, mental, and social well-being as well as their beliefs and behaviors related to treatment. Comprehensive support from families, communities, and healthcare providers is essential to assist patients in addressing treatment challenges and adverse ADRs. Rapid identification and strategies for monitoring and managing treatment challenges and ADRs can improve compliance and success of MDR-TB treatment. Keywords: Adverse Drug Reactions, Drug Side Effects, Multi Drug-Resistant Tuberculosis (MDR-TB), Treatment Success